THE IMPORTANCE OF RENAL BIOPSY IN PATIENTS WITH DIABETES MELLITUS - Ristovska, V; Dzekova Vidimliski, P; Shterjova Markovska, Zh; Milenkova Bogojevska M; Memedi, B; Stefanoska Taskoska, G; Stojanoska Severova, A; Janevski, Z (My University, 2024)
THE IMPORTANCE OF RENAL BIOPSY IN PATIENTS WITH DIABETES MELLITUS V. Ristovska, P. Dzekova-Vidimliski, Z. SterjovaMarkovska, M. Milenkova-Bogojevska, B. Memedi, G. Stefanoska-Taskoska, A. Stojanoska-Severova, Z. Janevski Deparment of Nephrology, Faculty of Medicine, University Sts. Cyril and Methodius Skopje, N. Macedonia PP Introduction. The diagnosis of diabetic kidney disease (DKD) is most often made clinically. However, there is growing awareness of the prevalence of nondiabetic kidney disease (NDKD) with or without concomitant diabetic nephropathy (DN) in patients with diabetes. Proteinuria and renal disfunction is common in patients with diabetes mellitus. In most of the cases diabetic nephropathy is the cause of that disfunction, but some of the cases present other nondiabetic renal disease. Renal biopsy in diabetic patients has presented variety of glomerular changes. Immunosuppresants used for treatment of the glomerular diseases may be associated with complications. Case report. Herein, we review the prevalence and presentation of NDKD in diabetic patients, with a focus on glomerular lesions, and discuss the ways in which diabetes can affect the diagnosis and management of these conditions. Diabetic patients with glomerular disease represent a sizable patient population. We report on 2 cases with diabetes mellitus with nondiabetic kidney disease confirmed with renal biopsy. The first case was a 58-year-old man, admitted to our Department with a history of diabetes, with actual presence of fatigue, inapetence and edema and proteinuria 6 g/24 hours. Renal function was diminished, creatinine values were 226 micromol/l, with GFR 38 ml/min. Second case was a 53 year -old-man with edema, hypertension, atrial fibriloflater and breatlessness, was treated with cardiologic therapy, but the edema was still present. Creatinin value was 126 micromol/l and proteinuria was 4,36 g/l (11,94g/ 24hours). In both cases, renal biopsy was performed and the histopatologic analysis showed membranoproliferaive glomeurlonephritis with presence of diabetic glomerulonephritis. The patients were treated with corticosteroids as pulse therapy, cyclophosphamide, diuretics and after that the clinical signs were stabilized. Conclusion. The authors suggest that the renal biopsy should be performed in diabetic patients with unusual features, such as proteinuria without other signs of diabetic disorders. Renal histology can be of fundamental importance to both treatment and prognosis of the disease
Keywords: RENAL BIOPSY; DIABETES MELLITUS